2007
DOI: 10.1002/ajmg.a.31842
|View full text |Cite
|
Sign up to set email alerts
|

The clinical utility of enhanced subtelomeric coverage in array CGH

Abstract: Telomeric chromosome abnormalities are a substantial cause of mental retardation and birth defects. Although subtelomeric fluorescence in situ hybridization (FISH) probes have been widely used to identify submicroscopic telomeric rearrangements, array-based comparative genomic hybridization (array CGH) has emerged as a more efficient and comprehensive detection method. Due to the clinical relevance of telomeric abnormalities, it has been proposed that array CGH using panels of BAC clones that map to regularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
7

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 30 publications
(36 reference statements)
4
82
0
7
Order By: Relevance
“…However, a single test, array CGH, detected all of the chromosomal copy number changes and simultaneously defined the chromosome breakpoints. In addition, high resolution oligonucleotide array CGH can detect complex subtelomeric rearrangements, such as the deletion of chromosome 7 in Subject A20, which may be missed by subtelomeric FISH panels that use single large clones to the most distal unique sequences (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, a single test, array CGH, detected all of the chromosomal copy number changes and simultaneously defined the chromosome breakpoints. In addition, high resolution oligonucleotide array CGH can detect complex subtelomeric rearrangements, such as the deletion of chromosome 7 in Subject A20, which may be missed by subtelomeric FISH panels that use single large clones to the most distal unique sequences (26).…”
Section: Discussionmentioning
confidence: 99%
“…There are two lines of evidence that imply that all chromosome 4p telomeres analyzed were healed by telomerase [Ballif et al, 2007]. In vitro studies have demonstrated that telomerase preferably adds a segment of the telomeric hexamer repeat unit onto a DNA fragment at its 3' end.…”
Section: Healing Of Broken Chromosomesmentioning
confidence: 99%
“…Terminal chromosomal deletions are the most common class of subtelomeric abnormalities and are often associated with mental retardation and multiple congenital anomalies [Ballif et al, 2007]. The most frequent terminal deletion syndromes include the 1p36 deletion syndrome (MIM 607872), the 4p terminal deletion leading to Wolf-Hirschhorn syndrome (MIM 194190), the 5p terminal deletions causing Cri-du-chat syndrome (MIM 123450), the 16p terminal deletion leading to alpha thalassaemia (MIM 141750), 9q34 deletion syndrome (MIM 610253) and the 22q terminal deletion syndrome (MIM 606232).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another assay that FISH permitted was the investigation of subtelomeric deletions and duplications, which were found to cause 2.5 to 5% of previously unexplained intellectual disability. [16][17][18] The more recent introduction of genomewide techniques to identify submicroscopic copynumber changes has revolutionized both the approach used in the laboratory to identify chromosome abnormalities that are responsible for intellectual disability and the diagnostic approach used in the clinic for patients with developmental delays or intellectual disability. The two techniques that are routinely used for discovery of copy-number changes are array CGH and SNP genotyping arrays, collectively referred to as chromosome microarrays (see text box).…”
Section: Copy-number Changes Deletions and Duplicationsmentioning
confidence: 99%